Pigment Dispersion
The A-B block copolymer-based pigment dispersion stabilizes inorganic pigments, addressing settling issues and enhancing redispersement, ensuring stable ejection and ink quality in inkjet printing.
Patent Information
- Application Number
- JP2024027505
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-02-27
AI Technical Summary
Conventional pigment dispersions containing inorganic pigments like titanium oxide tend to settle easily due to high specific gravity, forming hard cakes and are difficult to redisperse, and existing inkjet printers require special members to suppress sedimentation, limiting their versatility.
A pigment dispersion using an A-B block copolymer with specific molecular weights and compositions, adsorbed to inorganic pigments, maintaining dispersion stability and enabling easy redispersement, even with heavy specific gravity pigments.
The dispersion achieves stable ejection and excellent redispersibility, preventing sedimentation and maintaining ink quality over time, suitable for various inkjet printing applications.
Smart Images

Figure 0007612079000001 
Figure 0007612079000002 
Figure 0007612079000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pigment dispersion. [Background technology]
[0002] Conventionally, dyes have been used as coloring materials in aqueous inks for inkjet recording. However, in order to improve the water resistance and light resistance of the recorded images, pigments have been used instead of dyes. In order to prepare aqueous inks for inkjet recording that contain pigments as coloring materials, it is necessary to use a pigment dispersion in which the pigment is finely dispersed in order to prevent clogging of the nozzles of the recording head and to improve the color development of the images.
[0003] Conventionally, the white color of an image has been expressed by the color of the paper itself used as a recording medium. In order to express a white color with a higher whiteness, there is a tendency to use white ink obtained by using a white pigment dispersion liquid in which inorganic pigments such as titanium oxide pigments or hollow plastic beads are dispersed. Among them, titanium oxide pigments are used as inorganic pigments with high hiding power.
[0004] In order to maintain a good dispersion state of the pigment in the pigment dispersion and the aqueous ink obtained using the same, pigment dispersions and aqueous inks using various pigment dispersants have been proposed (Patent Documents 1 to 3). Also, an inkjet printer provided with a path for circulating the ink has been proposed in order to suppress the settling of the pigment in the ink (Patent Document 4). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 60-123564 [Patent Document 2] JP 2009-24165 A [Patent Document 3] JP 2017-39922 A [Patent Document 4] JP 2011-121344 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, even in low-viscosity pigment dispersions obtained by dispersing inorganic pigments such as titanium oxide pigments in an aqueous medium, inorganic pigments tend to settle easily due to their high specific gravity. Furthermore, the settled inorganic pigments tend to form hard cakes and are difficult to disperse again. Even in the pigment dispersions proposed in Patent Documents 1 to 3, the settling of inorganic pigments is not necessarily sufficiently suppressed, and there is room for improvement in redispersibility. In addition, in the case of the inkjet printer proposed in Patent Document 4, it is necessary to use special parts, etc. to improve the device, so there is a problem that it is poorly versatile.
[0007] The present invention has been made in consideration of the problems associated with the conventional techniques, and an object of the present invention is to provide a pigment dispersion liquid which is capable of preparing an aqueous inkjet ink having excellent ejection stability, which is less likely to cause sedimentation even when it contains an inorganic pigment having a heavy specific gravity, and has excellent re-dispersibility. [Means for solving the problem]
[0008] That is, according to the present invention, there is provided a pigment dispersion liquid as shown below. [1] A pigment dispersion liquid used for preparing an aqueous inkjet ink, the pigment dispersion liquid containing an inorganic pigment, a pigment dispersant, water, a water-soluble organic solvent, and an alkali, the pigment dispersant being an AB block copolymer having a polymer block A and a polymer block B, the number average molecular weight being 5,000 to 10,000, and the molecular weight distribution (weight average molecular weight / number average molecular weight) being 1.3 to 1.8, the polymer block A being 70 mass% or more of a structural unit (A-1) derived from cyclohexyl methacrylate, and a structural unit derived from at least one selected from the group consisting of methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate. a polymer block (A-2) having a number average molecular weight of 3,000 to 6,000 and a molecular weight distribution of 1.2 to 1.6, the polymer block B being a polymer block having a number average molecular weight of 1,000 to 6,000 containing 30 to 70 mass% of structural units (B-1) derived from methacrylic acid, 20 to 50 mass% of structural units (B-2) derived from cyclohexyl methacrylate, and a structural unit (B-3) derived from at least one member selected from the group consisting of methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate, the amount of the polymer block B in the AB block copolymer being 0.5 to 1.5 parts by mass per part by mass of the polymer block A. [2] The pigment dispersion according to [1], wherein the content of the inorganic pigment is 50 to 70 mass %, the content of the pigment dispersant is 2.5 to 10 parts by mass per 100 parts by mass of the inorganic pigment, the average particle size of the inorganic pigment is 180 to 300 nm, and the viscosity at 25°C is 5 to 20 mPa s. [3] The pigment dispersion according to [1] or [2], wherein the inorganic pigment is a titanium oxide pigment whose surface is treated with alumina. [4] The pigment dispersion according to any one of [1] to [3], wherein the solid content (mass %) of the upper layer after storage at 70°C for one week is 70% or more based on the solid content (mass %) before storage. Effect of the Invention
[0009] According to the present invention, it is possible to provide a pigment dispersion liquid which is capable of preparing an aqueous inkjet ink having excellent ejection stability, which is less likely to cause sedimentation even when it contains an inorganic pigment having a heavy specific gravity, and has excellent re-dispersibility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Pigment dispersion> Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. One embodiment of the pigment dispersion of the present invention is used for preparing an aqueous inkjet ink, and contains an inorganic pigment, a pigment dispersant, water, a water-soluble organic solvent, and an alkali. Hereinafter, the details of the pigment dispersion of this embodiment will be described.
[0011] (Inorganic pigments) Any inorganic pigment known in the art can be used as the inorganic pigment. Examples of the inorganic pigment include titanium oxide pigments, zinc oxide pigments, iron oxide pigments such as ochre and red iron oxide, zirconium oxide, copper oxide, yttria, molybdenum oxide, indium oxide, tin oxide, tungsten oxide, bismuth oxide, antimony oxide, and composite oxide pigments thereof, composite oxides of alkali metals such as lithium, sodium, and potassium with iron, manganese, cobalt, and nickel, composite oxides of alkaline earth metals such as magnesium, strontium, and calcium with iron, manganese, cobalt, and nickel, composite oxide pigments of cobalt, chromium, titanium, and aluminum, natural minerals such as clay and mica, and hollow silica pigments.
[0012] Examples of the shape of the inorganic pigment include a plate shape such as a glass plate, an indeterminate shape, and a particulate shape. In particular, from the viewpoint of the ejection properties of the inkjet ink, the inorganic pigment is preferably particulate in shape. The average particle diameter of the primary particles of the particulate inorganic pigment is preferably 50 to 300 nm. In this specification, the term "average particle diameter" refers to the average particle diameter (number average particle diameter) of 100 or more primary particles of the inorganic pigment measured and calculated using a transmission electron microscope.
[0013] The inorganic pigment may be previously surface-treated with a surface treatment agent, such as inorganic treatments including silica treatment, alumina treatment, silica-alumina treatment, and zirconia treatment, organic acid treatments including oleic acid treatment, and conventionally known silane coupling agent treatments and silazane treatments.
[0014] As the inorganic pigment for expressing white color in inkjet printing, it is preferable to use a white pigment, and more preferable to use a titanium oxide pigment having excellent hiding power.As the titanium oxide pigment, any titanium oxide pigment can be used regardless of the crystal system such as rutile type, anatase type, and brookite type, or the manufacturing method such as sulfuric acid method and chlorine method.Among them, it is preferable to use a rutile type titanium oxide pigment from the viewpoint of stability and availability.
[0015] In addition, titanium oxide pigments that have been inorganically or organically treated, such as silica-treated, alumina-treated, zirconia-treated, zinc-treated, silica-alumina-treated, silane coupling agent-treated, and alkanoic acid-treated, can be used. Among these, it is preferable to use titanium oxide pigments that have been surface-treated with alumina. Surface treatments with alumina include alumina treatment, silica-alumina treatment, and zirconia-alumina treatment. When titanium oxide pigments that have been surface-treated with alumina are used, the adsorptivity of pigment dispersants is improved, and the dispersion stability of inorganic pigments can be further improved.
[0016] From the viewpoint of enhancing the hiding power of the white color, the average particle diameter of the primary particles of the titanium oxide pigment is preferably 50 to 300 nm, more preferably 100 to 280 nm. If the average particle diameter of the titanium oxide pigment is less than 50 nm, the hiding power may be slightly insufficient and a sense of transparency may be obtained. On the other hand, if the average particle diameter of the titanium oxide pigment is more than 300 nm, it is difficult to make the particles fine even after dispersion treatment, and the filter or recording head may be easily clogged. If the average particle diameter is too large, the particles may easily settle, and the dispersion stability may be slightly reduced.
[0017] (Pigment dispersant) In conventional pigment dispersions, the storage stability of the pigment dispersant dissolved in water was not necessarily good. Therefore, the ejection stability, resolubility, and low viscosity of the inkjet ink prepared using this pigment dispersion were not always sufficient. In addition, inorganic pigments such as titanium oxide pigments tend to settle, and the settled inorganic pigments form hard cakes, making it difficult to disperse them again. It was difficult to sufficiently improve the performance of the inkjet ink prepared using such a pigment dispersion. As a result of the investigation, the present inventors found that a pigment dispersion capable of preparing an aqueous inkjet ink having sufficient performance can be obtained by using an AB block copolymer having a specific block structure as a pigment dispersant. That is, the pigment dispersant used in the pigment dispersion of the present embodiment is an AB block copolymer having a polymer block A (polymer chain A) and a polymer block B (polymer chain B).
[0018] The polymer block A is a water-insoluble polymer block. On the other hand, the polymer block B is a polymer block having a structural unit (B-1) derived from methacrylic acid, in which at least a part of the carboxyl groups are neutralized with an alkali to become water-soluble. Since the polymer block A is a water-insoluble polymer block, it is highly hydrophobic and easily interacts hydrophobically with a water-insoluble inorganic pigment. For this reason, the polymer block A is adsorbed to the inorganic pigment by hydrogen bonds or the like, and is hardly detached from the inorganic pigment. Furthermore, since the polymer block A is adsorbed to the inorganic pigment and the polymer block B is dissolved in water, the finely dispersed inorganic pigments sterically repel each other, and the finely dispersed state is maintained for a long period of time.
[0019] In addition, both polymer block A and polymer block B have structural units derived from cyclohexyl methacrylate. The action of the cyclohexyl group can improve the dispersion stability, sedimentation stability, and sedimentation recovery of the inorganic pigment over a long period of time. Polymer block A is adsorbed to the inorganic pigment by the action of the hydrophobic cyclohexyl group, and is difficult to detach from the inorganic pigment because it is a water-insoluble polymer block. While polymer block B is a polymer block that dissolves in water, the spread of the molecular chain into the water is suppressed because it has a cyclohexyl group. As a result, the inorganic pigment becomes in a state of being encapsulated by the pigment dispersant, which is an AB block copolymer.
[0020] The polymer block A contains a structural unit (A-1) derived from cyclohexyl methacrylate. The cyclohexyl group is highly hydrophobic, and therefore is well adsorbed to inorganic pigments such as titanium oxide pigments. By using the cyclohexyl group, which is stable, has a small molecular weight, and is available commercially, among cycloalkyl groups, it is possible to introduce a large number of cycloalkyl groups into the polymer block A. Furthermore, by introducing a large number of cycloalkyl groups into the polymer block A, it is possible to reduce the solubility in an aqueous medium containing a water-soluble organic solvent. Furthermore, it is possible to increase the glass transition point (Tg) (for example, to 50°C or higher), and it is possible to suppress detachment from the inorganic pigment. Note that methacrylates having cycloalkyl groups other than cyclohexyl groups (for example, cyclohexyl groups having an alkyl group, and cyclopolycyclic rings such as tricyclodecyl groups and isobornyl groups) may be too hydrophobic, and it may be difficult to introduce a large number of cycloalkyl groups into the polymer block A.
[0021] The content of the structural unit (A-1) derived from cyclohexyl methacrylate in the polymer block A is 70% by mass or more, and preferably 75 to 85% by mass. If the content of the structural unit (A-1) is less than 70% by mass, the hydrophobicity of the polymer block A decreases, and the structural unit may be easily detached from the inorganic pigment or dissolved in an aqueous medium, resulting in a decrease in the dispersion stability of the inorganic pigment.
[0022] The polymer block A contains a structural unit (A-2) derived from at least one selected from the group consisting of methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate. Among them, the structural unit (A-2) is preferably a structural unit derived from at least one selected from the group consisting of methyl methacrylate, which has a small carbon number and is unlikely to inhibit the properties of the polymer block A, and benzyl methacrylate, which has an aromatic ring and therefore has high adsorption to inorganic pigments. It is preferable that the polymer block A is substantially composed of only the structural unit (A-1) and the structural unit (A-2). By containing such a structural unit (A-2), the hydrophobicity of the cyclohexyl group, the solubility of the polymer block A in an aqueous medium, and the glass transition point (Tg) of the polymer block A are maintained, and the adsorption of the polymer block A to inorganic pigments can be increased. If a methacrylate other than methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate is used, the glass transition point (Tg) of the polymer block A may decrease or the affinity to water-soluble organic solvents may become too high. This may cause the polymer block A to be easily detached from the inorganic pigment, resulting in a slight decrease in dispersion stability.
[0023] Furthermore, when the polymer block A contains a structural unit derived from a hydrophilic group-containing methacrylate, such as a hydroxyl group-containing methacrylate such as 2-hydroxyethyl methacrylate, an ether group-containing methacrylate such as tetrahydrofurfuryl methacrylate and polyethylene glycol monomethyl methacrylate, or an amino group-containing methacrylate such as dimethylaminoethyl methacrylate, the hydrophobicity of the polymer block A is likely to decrease. This may result in a decrease in the adsorption of the pigment dispersant to the inorganic pigment, and the pigment dispersant may be detached from the inorganic pigment in an aqueous medium, which may lead to a decrease in the dispersibility of the inorganic pigment.
[0024] The number average molecular weight of the polymer block A is 3,000 to 6,000, and preferably 3,500 to 4,500. If the number average molecular weight of the polymer block A is less than 3,000, the molecular weight is small, resulting in a decrease in adsorption to inorganic pigments. On the other hand, if the number average molecular weight of the polymer block A is more than 6,000, it may become difficult to adsorb to inorganic pigments in a good state.
[0025] The molecular weight distribution of the polymer block A (weight average molecular weight / number average molecular weight) is 1.2 to 1.6, and preferably 1.25 to 1.55. That is, the molecular weight of the polymer block A is relatively uniform. It is industrially and practically difficult to produce a polymer block A having a molecular weight distribution of less than 1.2. On the other hand, if the molecular weight distribution of the polymer block A exceeds 1.6, the dispersion stability of the inorganic pigment decreases. In this specification, the number average molecular weight and weight average molecular weight are values measured by gel permeation chromatography (GPC) in terms of polystyrene.
[0026] The polymer block B contains a structural unit (B-1) derived from methacrylic acid. The content of the structural unit (B-1) derived from methacrylic acid in the polymer block B is 30 to 70% by mass, and preferably 35 to 65% by mass. If the content of the structural unit (B-1) is less than 30% by mass, the hydrophilicity of the polymer block B is insufficient, and the dispersion stability of the inorganic pigment in the aqueous medium decreases, and the redispersibility and sedimentation recovery decrease. On the other hand, if the content of the structural unit (B-1) exceeds 70% by mass, the hydrophilicity of the polymer block B becomes too high. As a result, the solubility in the aqueous medium increases, the viscosity of the ink prepared increases excessively, and the dispersion stability of the inorganic pigment decreases.
[0027] It contains a structural unit (B-2) derived from cyclohexyl methacrylate. The content of the structural unit (B-2) derived from cyclohexyl methacrylate in the polymer block B is 20 to 50% by mass, preferably 30 to 40% by mass. By setting the content of the structural unit (B-2) in the polymer block B within the above range, the polymer block B can be a water-soluble polymer block, and can have affinity for water while maintaining hydrophobicity. As a result, the inorganic pigment is encapsulated by the adsorbed pigment dispersant, and redispersibility and sedimentation recovery are exhibited. If the content of the structural unit (B-2) is less than 20% by mass, it becomes difficult to exert the effect of the cyclohexyl group. On the other hand, if the content of the structural unit (B-2) is more than 50% by mass, even if a large number of carboxy groups are present, the water solubility is insufficient, and the dispersion stability of the inorganic pigment decreases.
[0028] The polymer block B contains a structural unit (B-3) derived from at least one selected from the group consisting of methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate. In particular, the structural unit (B-3) is preferably a structural unit derived from at least one selected from the group consisting of methyl methacrylate and benzyl methacrylate. It is preferable that the polymer block B is substantially composed of only the structural unit (B-1), the structural unit (A-2), and the structural unit (B-3).
[0029] The number average molecular weight of the polymer block B is 1,000 to 6,000, preferably 1,500 to 4,500. The number average molecular weight (MnB) of the polymer block B is the value obtained by subtracting the number average molecular weight (MnA) of the polymer block A from the number average molecular weight (Mn) of the entire AB block copolymer (MnB=Mn-MnA). If the number average molecular weight of the polymer block B is less than 1,000, the molecular weight of the water-soluble polymer block is small, so that the dispersibility of the inorganic pigment becomes insufficient. On the other hand, if the number average molecular weight of the polymer block B is more than 6,000, the ratio of the water-soluble polymer block becomes excessive, so that the viscosity increases excessively or the water resistance decreases. That is, even if the polymer block A is adsorbed to the inorganic pigment, the water-soluble polymer block B is excessively large, so that the detachment of the AB block copolymer (pigment dispersant) from the inorganic pigment is promoted, and the dispersibility of the inorganic pigment becomes unstable.
[0030] The number average molecular weight of the AB block copolymer (pigment dispersant) is 5,000 to 10,000. If the number average molecular weight of the AB block copolymer is less than 5,000, it is easily detached from the inorganic pigment. On the other hand, if the number average molecular weight of the AB block copolymer is more than 10,000, the viscosity increases excessively during polymerization or the viscosity of the pigment dispersion increases excessively.
[0031] The molecular weight distribution of the AB block copolymer (weight average molecular weight / number average molecular weight) is 1.3 to 1.8, and preferably 1.35 to 1.6. If the molecular weight distribution of the AB block copolymer exceeds 1.8, many number average molecular weights outside the range will be contained, and the dispersibility of the inorganic pigment will decrease.
[0032] The amount of polymer block B in the AB block copolymer is 0.5 to 1.5 parts by mass, preferably 0.75 to 1.25 parts by mass, per part by mass of polymer block A. If the amount of polymer block B in the AB block copolymer is less than 0.5 parts by mass per part by mass of polymer block A, the hydrophilicity of the AB block copolymer is insufficient, and the AB block copolymer itself becomes particulate in the aqueous medium, resulting in insufficient adsorption to the inorganic pigment. On the other hand, if the amount of polymer block B in the AB block copolymer is more than 1.5 parts by mass per part by mass of polymer block A, even if the polymer block A is adsorbed to the inorganic pigment, the polymer block B is large and therefore easily detached, resulting in a decrease in the dispersion stability of the inorganic pigment.
[0033] (Production method of AB block copolymer) The AB block copolymer can be produced by a conventionally known living radical polymerization. Although it is difficult to obtain a copolymer having a block structure by normal radical polymerization, the living radical polymerization makes it possible to obtain an AB block copolymer having the desired block structure.
[0034] Examples of the living radical polymerization method include the nitroxide method (NMP method) that utilizes the dissociation and binding of amine oxide radicals; the atom transfer radical polymerization method (ATRP method) that uses heavy metals such as copper, ruthenium, nickel, and iron and ligands that form complexes with these heavy metals, and polymerizes using a halogen compound as an initiator compound; the reversible addition-fragmentation chain transfer polymerization method (RAFT method) that uses dithiocarboxylic acid esters and the like as initiator compounds and polymerizes using addition-polymerizable monomers and radical initiators; the TERP method that uses an organic tellurium compound as an initiator compound and ditelluride as a catalyst; the reversible transfer catalyst polymerization method (RTCP method, RCMP method) that uses at least one of iodine and an iodine compound as a polymerization initiator compound and uses a commercially available organic compound that can become a radical as a catalyst; etc. Among them, the TERP method, the RTCP method, and the RAFT method are suitable for molecular weight control and block structuring of methacrylate polymers, and the RTCP method, which uses an organic compound as a catalyst and has inexpensive raw materials, is particularly preferable.
[0035] After the formation of polymer block A, the desired methacrylate polymer can be obtained by adding monomers for forming polymer block B to form polymer block B. Note that polymer block A may be formed after the formation of polymer block B.
[0036] The AB block copolymer is preferably synthesized by solution polymerization. The solvent used in the solution polymerization is preferably the same as the water-soluble organic solvent used in the aqueous inkjet ink. Examples of the water-soluble organic solvent include alcohol-based solvents such as methanol, ethanol, and isopropanol; polyhydric glycol-based solvents such as ethylene glycol, propylene glycol, dipropylene glycol, glycerin, and 1,2-hexanediol; glycol ether-based solvents such as propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, dipropylene glycol monomethyl ether, and tripropylene glycol monomethyl ether; amide-based solvents such as pyrrolidone and 3-methoxy-N,N-dimethylpropionamide; and urea-based solvents such as tetramethylurea.
[0037] (dispersion medium) The pigment dispersion of this embodiment contains a liquid medium (aqueous medium) containing water and a water-soluble organic solvent as a dispersion medium for inorganic pigments. As the water, pure water, ion-exchanged water, soft water, etc. can be used. As the water-soluble organic solvent, there can be mentioned alcohol-based solvents such as methanol, ethanol, and isopropanol; polyhydric glycol-based solvents such as ethylene glycol, propylene glycol, dipropylene glycol, glycerin, and 1,2-hexanediol; glycol ether-based solvents such as propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, propylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, dipropylene glycol monomethyl ether, and tripropylene glycol monomethyl ether; amide-based solvents such as pyrrolidone and 3-methoxy-N,N-dimethylpropionamide; urea-based solvents such as tetramethylurea; and the like. Among them, it is preferable to use propylene glycol, glycerin, 1,2-hexanediol, diethylene glycol monobutyl ether, and triethylene glycol monobutyl ether, etc.
[0038] (alkali) The pigment dispersion of this embodiment contains an alkali. The carboxyl group in the polymer block B is neutralized and ionized by the alkali. This makes the polymer block B hydrophilic, and the inorganic pigment can be dispersed by the pigment dispersant. As the alkali, a conventionally known alkali can be used. Examples of the alkali include ammonia; organic amines such as dimethylaminoethanol and triethanolamine; and alkali metal hydroxides such as sodium hydroxide and potassium hydroxide.
[0039] The amount of alkali is preferably an amount that neutralizes the carboxyl groups in the pigment dispersant (AB block copolymer) to a neutralization rate of 110% or less. If the neutralization rate exceeds 110%, the pH of the pigment dispersion or ink may become too high due to the remaining alkali, which may cause deterioration of the components that make up the printer, etc.
[0040] After the AB block copolymer is formed by solution polymerization, it is preferable to add an alkaline aqueous solution to the polymerization reaction system to neutralize the formed AB block copolymer and turn it into an aqueous solution, whereby the formed AB block copolymer can be used as is in the pigment dispersion liquid without being taken out of the polymerization reaction system.
[0041] (Other additives) The pigment dispersion of this embodiment may contain other additives as necessary. Examples of other additives include organic solvents other than the water-soluble organic solvents described above, surfactants, preservatives, leveling agents, surface tension adjusters, pH adjusters, UV absorbers, light stabilizers, antioxidants, dyes, fillers, waxes, thickeners, defoamers, mildew inhibitors, antistatic agents, and binder components. Examples of surfactants include silicone-based, acetylene glycol-based, fluorine-based, alkylene oxide-based, and hydrocarbon-based surfactants. Examples of preservatives include sodium benzoate, benzimidazole, thiabendazole, potassium sorbitanate, sodium sorbitanate, sodium dehydroacetate, thiazosulfamide, and pyridinethiol oxide.
[0042] (Pigment dispersion) The content of the inorganic pigment in the pigment dispersion is preferably 50 to 70% by mass, and more preferably 55 to 65% by mass. By making the content of the inorganic pigment such a high percentage, the amount of the pigment dispersion to be blended when preparing an aqueous inkjet ink can be reduced, and the degree of freedom in designing the ink blend can be increased. If the content of the inorganic pigment in the pigment dispersion is less than 50% by mass, the ink manufacturing cost increases and the degree of freedom in designing the ink tends to decrease. On the other hand, if the content of the inorganic pigment exceeds 70% by mass, the ink tends to become highly viscous, and may be difficult to disperse.
[0043] The content of the pigment dispersant in the pigment dispersion is preferably 2.5 to 10 parts by mass, more preferably 3 to 7.5 parts by mass, based on 100 parts of the inorganic pigment. If the content of the pigment dispersant is too low, the dispersion stability of the inorganic pigment may be slightly reduced. On the other hand, if the content of the pigment dispersant is too high, components that do not contribute to dispersion will be present in excess, and the viscosity of the pigment dispersion or ink will tend to increase. Furthermore, the excess pigment dispersant will tend to become a binder component of the hard cake formed by the sedimentation of the inorganic pigment, and redispersibility and sedimentation recovery may tend to decrease.
[0044] The pigment dispersion can be produced according to a conventional method. When mixing, stirring, and dispersing, a conventional mixer, stirring device, and dispersing device can be used. Examples of the stirrer include a dissolver and a homogenizer. Examples of the mixer and dispersing device include a kneader, an attritor, a ball mill, a vertical media dispersing device and a horizontal media dispersing device loaded with glass beads or zirconia beads, a colloid mill, a jet mill, a high-pressure homogenizer, and an ultrasonic dispersing device. In addition, it is preferable to use beads of 1 mm or less as the media loaded in the media dispersing device. By using such beads as the media, the crystals and shape of the inorganic pigment are less likely to be destroyed, and so-called soft dispersion can be achieved.
[0045] It is preferable to disperse the inorganic pigment into primary particles by the above-mentioned mixing, stirring, and dispersion treatment. However, the inorganic pigment may be aggregated to a required particle size. The dispersion state of the inorganic pigment can be confirmed by a conventionally known method. For example, it can be confirmed by using an optical microscope or an electron microscope, by measuring with a particle size distribution measuring device such as light scattering, or by measuring absorbance using a spectrophotometer. After the dispersion treatment, coarse particles may be removed by centrifugal filtration, filter filtration, or the like. Thereafter, by adding other additives, etc. as necessary, a pigment dispersion liquid can be obtained.
[0046] The average particle diameter of the inorganic pigment in the pigment dispersion is preferably 180 to 300 nm, more preferably 200 to 280 nm. By setting the average particle diameter of the inorganic pigment in the pigment dispersion within the above range, the hiding power of the resulting ink can be increased. If the average particle diameter of the inorganic pigment is less than 180 nm, the hiding power may be insufficient. On the other hand, if the average particle diameter of the inorganic pigment is more than 300 nm, clogging of the filter or recording head is likely to occur. In addition, the inorganic pigment is likely to settle in the pigment dispersion or ink, and the smoothness and sharpness of the resulting image (printed matter) are likely to decrease. The average particle diameter of the inorganic pigment in the pigment dispersion is a number average particle diameter measured using a particle diameter measuring device by light scattering.
[0047] The viscosity of the pigment dispersion at 25°C is preferably 5 to 20 mPa·s, and more preferably 5 to 15 mPa·s. If the viscosity of the pigment dispersion is less than 5 mPa·s, the settling of the inorganic pigment may be promoted. On the other hand, if the viscosity of the pigment dispersion is more than 20 mPa·s, the viscosity of the prepared ink may be easily increased.
[0048] The pigment dispersion preferably has a surface tension of 20 to 40 mN / m at 25° C. The pigment dispersion preferably has a pH of 7.5 to 10.0 at 25° C., and more preferably 8.0 to 9.9.
[0049] The pigment dispersion of the present embodiment is less likely to produce sedimentation even though it contains an inorganic pigment with a high specific gravity. Specifically, the solid content (mass%) of the upper layer after storage at 70°C for one week is preferably 70% or more, and more preferably 80% or more, based on the solid content (mass%) before storage. Here, the "upper layer" refers to the portion above half the height of the pigment dispersion after storage.
[0050] Furthermore, the pigment dispersion of this embodiment is unlikely to produce sediment even after a long period of time, but even if sediment does form, it can be returned to its original dispersed state by a simple operation such as stirring. It is believed that the use of an AB block copolymer having a polymer block B with controlled water solubility as a pigment dispersant encapsulates the inorganic pigment and places ionized carboxy groups on the surface of the inorganic pigment, thereby improving sedimentation stability and sedimentation recovery.
[0051] (Use of pigment dispersion) The pigment dispersion of the present embodiment is useful as a pigment dispersion to be incorporated into an aqueous inkjet ink. The printing method using the aqueous inkjet ink is not particularly limited, and examples thereof include a thermal method and a piezoelectric method. The type of inkjet printer is also not particularly limited, and the inkjet printer can be applied to an office inkjet printer, an industrial inkjet printer, an inkjet printer for textile printing, a high-speed printer, and the like. EXAMPLES
[0052] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.
[0053] <Synthesis of pigment dispersant> (Synthesis Example 1) Diethylene glycol monobutyl ether (BDG) 141.3 parts, iodine 1.0 parts, 2,2'-azobis (4-methoxy-2,4-dimethylvaleronitrile) (FUJIFILM Corporation, V-70) 3.8 parts, cyclohexyl methacrylate (CHMA) 44.1 parts, benzyl methacrylate (BzMA) 18.5 parts, and N-iodophthalimide (NIS) 0.05 parts were placed in a reaction vessel. The mixture was heated to 45°C while flowing nitrogen, and stirred, and polymerized for 4 hours to form a polymer block A (polymer). A part of the obtained liquid was sampled, and the polymerization conversion rate calculated from the non-volatile content that reached a constant weight at 180°C was about 100%. In addition, when the sampled liquid was dissolved in acetone and analyzed by gas chromatography, almost no monomer was detected. The molecular weight of the polymer was measured by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a developing solvent. As a result, the number average molecular weight (Mn) of the polymer calculated as polystyrene was 4,700, and the molecular weight distribution (PDI=weight average molecular weight (Mw) / number average molecular weight (Mn)) was 1.31.
[0054] After cooling to 40°C, 11.8 parts of CHMA, 13.9 parts of MMA, and 22.5 parts of methacrylic acid (MAA) were added and polymerized for 4 hours to form polymer block B, thereby obtaining an AB block copolymer. It was confirmed that the polymerization system had increased in viscosity.
[0055] The Mn measured by GPC was 9,100, and the PDI was 1.39. Since the molecular weight was increased compared to polymer block A, it is believed that an AB block copolymer was formed. The Mn of polymer block B ("Mn of AB block copolymer" - "Mn of polymer block A") was 4,400. The ratio of the amount of monomer constituting polymer block A to the amount of monomer constituting polymer block B (mass ratio = A / B) was calculated to be 1 / 0.77.
[0056] Next, a mixture of 10.7 parts of sodium hydroxide and 245.5 parts of ion-exchanged water (aqueous sodium hydroxide solution) was added to obtain a transparent, viscous solution of pigment dispersant D-1. The solid content of the obtained solution was 22.9%, and the pH was 9.9.
[0057] (Synthesis Examples 2 to 9) Solutions of pigment dispersants D-2 to D-9 were obtained in the same manner as in Synthesis Example 1, except that various materials were used in the types and amounts (unit: parts) shown in Tables 1 to 3. The meanings of the abbreviations in the table are as follows. tBMA: t-Butyl methacrylate EMA: Ethyl methacrylate PPG: Propylene glycol monopropyl ether
[0058] TIFF0007612079000001.tif174170
[0059] TIFF0007612079000002.tif168170
[0060] TIFF0007612079000003.tif182170
[0061] (Comparative Synthesis Example 1) An AB block copolymer was formed in the same manner as in Synthesis Example 4 above, except that isobornyl methacrylate was used instead of BzMA. The resulting AB block copolymer had an Mn of 9,200 and a PDI of 1.32. The Mn of polymer block B was 4,100. When an aqueous sodium hydroxide solution was added in the same manner as in Synthesis Example 4 above, the solution became cloudy and some of it precipitated. It is believed that the polymer block A was too hydrophobic to be converted into an aqueous solution. From the above, it was determined that the resulting AB block copolymer could not be used as a pigment dispersant.
[0062] (Comparative Synthesis Example 2) 141.3 parts of BDG was placed in a reaction vessel and heated to 80°C. A mixture of 55.9 parts of CHMA, 18.5 parts of BzMA, 13.9 parts of MMA, 22.5 parts of MAA, 3 parts of azobisisobutyronitrile, and 2.0 parts of thioglycerol was placed in a dropping device, and after adding 1 / 3 of the amount, the remaining amount was dropped over 2 hours. Polymerization was carried out at 80°C for 7 hours to form a random copolymer. The Mn of the resulting random copolymer was 8,600 and the PDI was 1.89. Next, an aqueous sodium hydroxide solution was added in the same manner as in the above-mentioned Synthesis Example 1 to make it into an aqueous solution, and a solution of a pigment dispersant HD-1 that was transparent and viscous was obtained. The solid content of the resulting solution was 22.9% and the pH was 9.8.
[0063] (Comparative Synthesis Examples 3 to 6) Solutions of pigment dispersants HD-2 to HD-5 were obtained in the same manner as in Synthesis Example 1 above, except that various materials were used in the types and amounts (unit: parts) shown in Table 4. The meanings of the abbreviations in the table are as follows. ·BMA: Butyl methacrylate
[0064] TIFF0007612079000004.tif170170
[0065] <Production of pigment dispersion (1)> Example 1 270 parts of water and 100 parts of pigment dispersant D-1 solution were mixed and homogenized, and then 15 parts of BDG and 15 parts of PPG were added and homogenized. 400 parts of CI Pigment White 6 (trade name "JR-600A", manufactured by Teika Co., Ltd., primary average particle size: 0.25 μm, alumina surface treated) were added, and the mixture was obtained by thoroughly stirring and mixing using a dissolver. The mixture (mill base) obtained was dispersed at a peripheral speed of 7 m / s using a horizontal media disperser (trade name "Dyno Mill 0.6 liter ECM type", manufactured by Shinmaru Enterprises Co., Ltd., zirconia bead diameter: 0.5 mm) to thoroughly disperse the pigment. The mixture was filtered through a 10 μm membrane filter to remove coarse particles, and a white pigment dispersion W-1 with a pigment concentration of 50% was obtained. The amount of pigment dispersant per 100 parts of pigment was 5.75 parts. The average particle size of the pigment was 281 nm, and the viscosity was 9.9 mPa·s. The solid content was calculated from the residue obtained by heating in a thermostatic chamber at 150°C until a constant weight was reached, and was found to be 52.7%.
[0066] (Examples 2 to 9, Comparative Examples 1 to 5) Pigment dispersions W-2 to 9 and HW-1 to 5 were obtained in the same manner as in Example 1 above, except that solutions of the pigment dispersants shown in Tables 5-1 and 5-2 were used.
[0067] <Evaluation> (sedimentation stability) The pigment dispersion was poured into a screw-top test tube with a diameter of 10 mm and a length of 150 mm to a height of 100 mm, and stored in a thermostatic chamber at 70°C for one week. After storage, a portion of the upper layer (above 1 / 2 height) was taken and the solid content was measured. The solid content retention rate was calculated from the following formula (1), and the sedimentation stability of the pigment dispersion was evaluated according to the following evaluation criteria. The results are shown in Tables 5-1 and 5-2. "Solid content retention rate (%)" = {(solid content of upper layer after storage) / (solid content immediately after production)} × 100 (1) ⊚: The solid content retention rate was 90% or more and 100% or less. ◯: The solid content retention rate was 70% or more and less than 90%. Δ: The solid content retention rate was 50% or more and less than 70%. ×: The solid content retention rate was less than 50%.
[0068] (Settling recovery) The pigment dispersion was poured into a screw-top test tube with a diameter of 10 mm and a length of 150 mm to a height of 100 mm, and stored in a thermostatic chamber at 70°C for one week. After storage, the tube was shaken at 150 rpm for 15 seconds using a mini shaker, and a portion was sampled and the solid content was measured. The sedimentation recovery rate was calculated using the following formula (2), and the sedimentation recovery property of the pigment dispersion was evaluated according to the following evaluation criteria. The results are shown in Tables 5-1 and 5-2. "Subsidence recovery rate (%)" = {(solid content after shaking) / (solid content immediately after production)} × 100 (2) ○: The sedimentation recovery rate was 90% or more and 100% or less. ×: Sedimentation recovery rate was less than 90%.
[0069] (Redispersibility) The viscosity of the pigment dispersion after shaking obtained in the above evaluation of "sedimentation recovery property" and the average particle size of the pigment were measured. The redispersibility of the pigment dispersion was then evaluated according to the following evaluation criteria. The results are shown in Tables 5-1 and 5-2. ◯: The average particle size after shaking was within ±20 nm of the average particle size immediately after production, and the change in viscosity was less than ±1 mPa·s. ×: The average particle size after shaking was outside the range of ±20 nm of the average particle size immediately after production, or the viscosity change was ±1 mPa·s or more.
[0070] (Discharge stability) 16 parts of pigment dispersion, 16.8 parts of binder component, 5 parts of 1,2-hexanediol, 13 parts of propylene glycol, 1 part of surfactant (trade name "Surfynol 465", manufactured by Nissin Chemical Co., Ltd.), and 49.2 parts of water were mixed and thoroughly stirred, and then filtered through a membrane filter with a pore size of 10 μm to prepare inkjet inks IW-1 to 9 and HIW-1 to 5. As the binder component, a polymethacrylate-based emulsion (emulsion containing polymethacrylate, solid content: 30.8%) described in "Example 14" of Japanese Patent No. 6967168 was used. The obtained inks were filled into cartridges, which were then installed in an inkjet printer (trade name "MMP-813", manufactured by Mastermind Co., Ltd.), and a solid image was printed on a PET film (polyethylene terephthalate film, manufactured by Futamura Chemical Co., Ltd., thickness: 60 μm). The ink ejection stability during printing was evaluated according to the following evaluation criteria, and the results are shown in Tables 5-1 and 5-2. ◯: Discharge was possible without any problems, and a good image was printed. △: Scattering of minute droplets was observed. ×: When ejected, droplets splashed and scattered, causing image disturbance.
[0071] (Image whiteness) The print obtained in the above evaluation of "ejection stability" was placed on black stripe-shaped paper. Then, using a spectrophotometer, the L value of the image in the area corresponding to the black stripe was measured, and the whiteness of the image was evaluated according to the evaluation criteria shown below. The higher the L value, the better the hiding power. The results are shown in Tables 5-1 and 5-2. ◎: L value was 75 or higher. ○: L value was 60 or more and less than 75. ×: L value was less than 60.
[0072] TIFF0007612079000005.tif167170
[0073] TIFF0007612079000006.tif168170
[0074] <Production of pigment dispersion (2)> Example 10 A brown pigment dispersion with a pigment concentration of 50% was obtained in the same manner as in Example 1 described above, except that red iron oxide pigment (product name "Todacolor 120ED", manufactured by Toda Kogyo Co., Ltd., average primary particle size: 0.14 μm) was used instead of CI Pigment White 6. The average particle size of the pigment was 290 nm, the viscosity was 15.6 mPa s, and the solid content was 52.6%. When the "sedimentation stability" described above was evaluated, the solid content of the upper layer was 40.6%, and the solid content maintenance rate was 77.2%. This confirmed that the product exhibited good sedimentation stability.
[0075] Example 11 A black pigment dispersion with a pigment concentration of 50% was obtained in the same manner as in Example 1 described above, except that a black complex oxide (product name "Dipyroxide TM3550", manufactured by Dainichiseika Color & Chemicals Co., Ltd., primary average particle size: 60 nm) was used instead of CI Pigment White 6. The average particle size of the pigment was 198 nm, the viscosity was 18.4 mPa·s, and the solid content was 52.6%. In addition, when the aforementioned "sedimentation stability" was evaluated, the solid content of the upper layer was 48.9%, and the solid content maintenance rate was 92.9%. This confirmed that the product exhibited good sedimentation stability. [Industrial Applicability]
[0076] The pigment dispersion of the present invention is useful as a pigment dispersion used for preparing an aqueous inkjet ink. In addition, the ink prepared using the pigment dispersion of the present invention has excellent ejection stability, and when a white inorganic pigment such as a titanium oxide pigment is used, an image with high whiteness can be recorded. Therefore, the ink prepared using the pigment dispersion of the present invention is suitable not only for personal and office use, but also for industrial inkjet printing such as packaging film printing and high-speed printing, and can also be applied in the field of printing inks such as aqueous paints for automobiles or building materials, aqueous stationery, aqueous gravure inks, and aqueous flexo inks.
Claims
1. A pigment dispersion liquid used for preparing an aqueous inkjet ink, comprising an inorganic pigment, a pigment dispersant, water, a water-soluble organic solvent, and an alkali, the pigment dispersant is an A-B block copolymer consisting of a polymer block A and a polymer block B, having a number average molecular weight of 5,000 to 10,000 and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.3 to 1.8; the polymer block A is a polymer block containing 70% by mass or more of a structural unit (A-1) derived from cyclohexyl methacrylate and a structural unit (A-2) derived from at least one member selected from the group consisting of methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate, and having a number average molecular weight of 3,000 to 6,000 and a molecular weight distribution of 1.2 to 1.6; the polymer block B is a polymer block having a number average molecular weight of 1,000 to 6,000, which contains 30 to 70% by mass of a structural unit (B-1) derived from methacrylic acid, 20 to 50% by mass of a structural unit (B-2) derived from cyclohexyl methacrylate, and a structural unit (B-3) derived from at least one member selected from the group consisting of methyl methacrylate, ethyl methacrylate, t-butyl methacrylate, and benzyl methacrylate; The pigment dispersion liquid, wherein the amount of the polymer block B in the AB block copolymer is 0.5 to 1.5 parts by mass per 1 part by mass of the polymer block A.
2. The pigment dispersion liquid according to claim 1, wherein the content of the structural unit (A-1) in the polymer block A is 75 mass% or more.
3. The pigment dispersion liquid described in claim 1, wherein the structural unit (A-2) is a structural unit derived from at least one selected from the group consisting of methyl methacrylate and benzyl methacrylate.
4. The content of the inorganic pigment is 50 to 70 mass %, The content of the pigment dispersant is 2.5 to 10 parts by mass relative to 100 parts by mass of the inorganic pigment, The inorganic pigment has an average particle size of 180 to 300 nm; 2. The pigment dispersion according to claim 1, which has a viscosity at 25° C. of 5 to 20 mPa·s.
5. 2. The pigment dispersion according to claim 1, wherein the inorganic pigment is a titanium oxide pigment whose surface has been treated with alumina.
6. 6. The pigment dispersion according to claim 1, wherein the solid content (mass %) of the upper layer after storage at 70° C. for one week is 70% or more based on the solid content (mass %) before storage.
Citation Information
Patent Citations
Aqueous pigment dispersion
JP1985123564A
Pigment dispersant, its production process, and its use
JP2009024165A
Inkjet printer
JP2011121344A
Aqueous white ink for inkjet recording, white pigment paste, and aqueous ink set for inkjet recording
JP2013082885A
Aqueous ink for inkjet recording
JP2017039922A